TERAPI OPERATIF VERSUS TERAPI KONSERVATIF FRAKTUR STRES CALCANEUS TINJAUAN LITERATUR SISTEMATIS: Uji Coba Kontrol Acak - Rr. Puspa Buana Sari Sri Maharani, (2021)
Calcaneus stress fracture is the second leading cause of disability in all athletes. Stress fractures that are not intervened promptly can increase the risk of developing a displaced calcaneus fracture. Displaced calcaneal fracture that can cause the most common loss is DIACF (Displaced Intra-Articular Calcaneal Fracture). The treatment that can be given so far is still a matter of controversy. The investigators conducted a literature study regarding operative therapy versus conservative therapy of intra-articular calcaneus fractures in athletes. This study proved that there was a significant improvement in the group using non-operative therapy compared to operative therapy. Method: Systematic Review by conducting literature searches using PubMed and Science Direct. Furthermore, the journal's eligibility costs are carried out to answer the questions that are the focus of this research. The literature used is based on clinical trials on intraarticular calcaneal fractures with a randomized controlled trial design. Results: Based on 3 studies that the overall complication rate in the nonoperative group was significantly lower than the surgery group (p = 0.01). These complications include pain when walking, difficulty wearing shoes, infection, until the operation returns. Conclusion: Non-operative therapy has been shown to be more effective and safer for patients with displaced intra-articular calcaneus fractures, evaluated for the lower risk of complications after intervention with non-operative therapy.